Capitalism, Hegemony and Violence in the Age of Drones - Pollack, Norman (Springer International Publishing, 2018)
This book offers a critical analysis of the rise of the US to global hegemony against a background of increased erosion of democracy and rule of law, and a rising linear pattern of near-absolute capitalist development. The author argues that the significant shrinkage of the ideological spectrum globally, as a result of worrisome levels of business and government interpenetration, has created a dangerous 'prefascist configuration' whereby unthinkable levels of violence have been normalized through the use of technologies such as drones, increasingly condoned even by 'liberal' groups and the so-called political left. Using the example of the Obama administration and its increased reliance on drone assassinations, the volume makes a case for the dangers that lie in today's unique convergence of lack of transparency in government, business-government interpenetration, informal social regimentation, and militarization of capitalism.